Pop-up Books in The Snowball-Throwing Learning Model Compared to Fifth-Grade Students - Khairul Respaningsih; Minsih (International Journal of Elementary Education, 2023)
The learning outcomes of social studies subjects obtained by students were not as expected. In order to solve this problem it is requires learning model and appropriate media to support social studies in grade V MI students. The purpose of the study was to analyses the efficacy of employing pop-up book medium in the snowball-throwing learning paradigm for fifth-grade MI students' social studies learning outcomes. This study utilizes quantitative research using a proper experimental design and a pre- and post-test control group design. 50 fifth-grade students participated in this study, 20 in the treatment group and 20 in the control group. In this study, the independent variable (X) is the pop-up book media and the snowball-throwing learning model, while the dependent variable (Y) is students of V grade MI learning results. This study's data analysis approach utilized a precondition test, specifically the initial and final normality tests, to determine whether or not the data were normally distributed, while the hypothesis test employed a one-sided T test. The results show that there are differences in student learning outcomes in the experimental class using pop-up book media in the snowball throwing learning model compared with the control class using conventional learning methods.